2017
DOI: 10.1021/acs.biochem.7b00666
|View full text |Cite
|
Sign up to set email alerts
|

Protein Assembly and Building Blocks: Beyond the Limits of the LEGO Brick Metaphor

Abstract: Proteins, like other biomolecules, have a modular and hierarchical structure. Various building blocks are used to construct proteins of high structural complexity and diverse functionality. In multidomain proteins, for example, domains are fused to each other in different combinations to achieve different functions. Although the LEGO brick metaphor is justified as a means of simplifying the complexity of three-dimensional protein structures, several fundamental properties (such as allostery or the induced-fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 80 publications
2
31
0
Order By: Relevance
“…53 The data obtained by HDX experiments is still difficult to interpret [41] and results 54 of other experiments or techniques are tedious to compare [29,39]. The Start2Fold 55 database [39] provides an invaluable annotation of EFR which became protected early 56 in a standardized manner [29]. In a previous study [38], EFR have been shown to 57 exhibit lower disorder scores and higher backbone rigidity.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…53 The data obtained by HDX experiments is still difficult to interpret [41] and results 54 of other experiments or techniques are tedious to compare [29,39]. The Start2Fold 55 database [39] provides an invaluable annotation of EFR which became protected early 56 in a standardized manner [29]. In a previous study [38], EFR have been shown to 57 exhibit lower disorder scores and higher backbone rigidity.…”
mentioning
confidence: 99%
“…87 Graph representations of proteins also allow to assess whether proteins feature a 88 3/18 modular design [54,55]. Reinvention is rarely observed in nature and whenever possible 89 existing, established, and safe strategies are reused [56]. This can explain why the 90 conceivable sequence and structure space is explored so little: by evolving established 91 sequences, misfolding sequences or those prone to aggregation are avoided [56,57].…”
mentioning
confidence: 99%
See 3 more Smart Citations